Archetyp improwizacji organizacyjnej : poszerzenie architektury zarządzania strategicznego - Bratnicki, Mariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Theories of strategic competition emphasize the organization's ability to cope with uncertainty as the source of value and wealth creation. The author attempt to bring convergent elements of major contemporary management theories into this forum by introducing a framework of organizational archetypes strategic planning, organizational learning, corporate entrepreneurship, and organizational improvisation - that are derived from unique configurations of key processes, logic of change, critical levers of effectiveness and main management tasks, a set of strategic instruments. The author demonstrates the utility of organizational archetypes framework by showing how it can refine organizational improvisation theory. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 198-203